2016
DOI: 10.17770/sie2016vol3.1474
|View full text |Cite
|
Sign up to set email alerts
|

Women`s Motivation to Engage With the Nordic Walking

Abstract: Physical activity beneficial effects on human health in various aspects are proved  by many research. In woman's health status maitenance and strengthening the important role has physical activitities. People engage with physical activities encourages a number of factors. Nordic walking as a physical activity has many benefits that would motivate women of different ages to engage with the Nordic walking. The research group was formed of 100 women between the ages of 25 -82 years. According to the World Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Thus, sport is a means of maintaining a state of relaxation of body and mind and contributes to a person’s well-being. The reduction of stress and weight adjustment are the main factors that motivate participation in NW training; however, for older people, it is also a great opportunity to socialize [36]. Involvement in NW training significantly affects levels of health self-assessments [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sport is a means of maintaining a state of relaxation of body and mind and contributes to a person’s well-being. The reduction of stress and weight adjustment are the main factors that motivate participation in NW training; however, for older people, it is also a great opportunity to socialize [36]. Involvement in NW training significantly affects levels of health self-assessments [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…From the sources of current literature, it can be concluded that men and women have different levels of physical activity, and these differences expose women to a variety of serious health problems and consequences (Skidmore & Carson, 2016). Physical activities play an important role in strengthening women's health (Upeniece, Vinberga, Arnis, & Erts, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…PVO aptaukošanos definē kā sarežģītu multifaktoriālu hronisku slimību, kas rodas ģenētisku un vides faktoru mijiedarbības ietekmē (PVO, 2008). Būtiski meklēt fiziskās aktivitātes, kas būtu sabiedrībā populāras, mazāk simptomus izraisošas un līdz ar to stimulētu cilvēku iesaisti tajās (Upeniece et al, 2016).…”
Section: Introductionunclassified
“…Kā viena no šādām aktivitātēm ir NW, kas daudzviet ieguvusi popularitāti dažādās vecuma grupās un it īpaši vecākās paaudzes sievietes patiesi motivētas nodarboties ar NW (Upeniece et al, 2016). Sieviešu vidū popularitāti guvuši arī citi fiziskās aktivitātes veidi, tādi kā tradicionālās pastaigas (turpmāk tekstā soļošana), ūdens aerobika, Pilates.…”
Section: Introductionunclassified
See 1 more Smart Citation